An Improved Multi-Cycle Deadlock Detection and Resolution Algorithm for Distributed Systems - Mohsen Askari; Rozita Jamili Oskouei (Computer Engineering and Applications Journal, 2014)
Distributed systems exhibit a high degree of resource and data sharing creating a state in which deadlocks might make their appearance. Since deadlock detection and resolution  is one of the important concerns in distributed systems which lead to minimizing available resources, therefore instigating   the  system  throughput decrease.  Our  proposed algorithm detects and resolves  the  multi-cycle  deadlocks, whether the initiator is involved in the deadlock cycle directly or indirectly. Also the chance  of  phantom  deadlock  detection is minimized. This  algorithm  not  only  can manage the simultaneous execution of it but also detects the multi-cycle deadlocks in  the  distributed  systems. Our  algorithm introduces a modified probe and victim message  structure. Moreover,  no  extra  storage  required  to  store  prob message  in each node which is known as memory overhead in the distributed systems.